The Role of Digital Innovation in Increasing the Inclusiveness of Village Development - Ghufron Fadil Ahmad; Musthafa Karim (Kampret Journal, 2026)
Digital innovation has become a key driver of rural transformation by enabling village governments to improve public service delivery, strengthen governance, and promote sustainable development. At the same time, inclusive village development has emerged as a critical policy objective to ensure that all community members, including vulnerable and marginalized groups, can equally participate in and benefit from development initiatives. However, persistent challenges such as unequal internet access, low digital literacy, limited digital infrastructure, and uneven community participation continue to hinder the realization of inclusive digital transformation in rural areas. This study aims to analyze the role of digital innovation in enhancing the inclusiveness of village development and to identify the factors that support and hinder its implementation. A quantitative research design with an explanatory survey approach was employed in several digitally developing villages in Indonesia. Primary data were collected through structured questionnaires administered to village residents, while secondary data were obtained from government reports and official village documents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationship between digital innovation and inclusive village development. The findings reveal that digital innovation significantly improves access to public services, increases community participation, enhances governance transparency, and strengthens community empowerment. The findings contribute to the literature on digital governance and inclusive rural development while providing practical recommendations for policymakers and village governments seeking to implement sustainable and inclusive digital transformation strategies.